2014
DOI: 10.1080/1062726x.2014.956104
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Engagement in Corporate Social Responsibility: A Meta-Level Construal of Engagement

Abstract: Organizations are increasingly seeking stakeholder support through engagement to demonstrate their corporate social responsibility (CSR) credentials. These credentials are, in turn, used to support claims of legitimacy for organizational operations. This article uses a process model of antecedents, implementation, and consequences to study the connection between engagement and CSR. CSR reports show organizations perceive engagement in CSR as both communication and activities between organizations and their sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 67 publications
1
74
0
3
Order By: Relevance
“…Farmers confirmed that empowerment actions are necessary to increase the benefits of participating to value co-creation projects [7,8,38,39]. They also underlined that value co-creation projects are crucial to moderate vulnerabilities within the supply chain and in their everyday life, because taking part to such projects favor the sharing of interests [16], their involvement in business decisions [30], and their awareness through effective dialogue [31,32].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Farmers confirmed that empowerment actions are necessary to increase the benefits of participating to value co-creation projects [7,8,38,39]. They also underlined that value co-creation projects are crucial to moderate vulnerabilities within the supply chain and in their everyday life, because taking part to such projects favor the sharing of interests [16], their involvement in business decisions [30], and their awareness through effective dialogue [31,32].…”
Section: Discussionmentioning
confidence: 80%
“…The challenge is to cope with unexpected events and their consequences while continuing to create value for all stakeholders [12,13]. For this reason, the concepts of value creation and value co-creation are central to moderate vulnerabilities through a joining of interest among stakeholders [16], the involvement of stakeholders in business decisions [30], and by establishing effective dialogue, decision sharing, and actions [31,32].…”
Section: Resilience and Value Co-creationmentioning
confidence: 99%
“…The synergies between CSR and stakeholder engagement have provided a rich setting for the growth of a body of literature that seeks to define and characterize engagement (Devin & Lane, 2014). Indeed, the domain of CSR has et al, 2014).…”
Section: T He Concept Of Csr Has Undergone Significant Change Since Imentioning
confidence: 99%
“…This push to become more attuned to stakeholder expectations means more and more organizations are undertaking stakeholder engagement as part of their CSR activities. Organizations engage with stakeholders to identify (and perhaps meet) their expectations, and to communicate how they are being responded to (Devin & Lane, ; Dobele et al ., ). By engaging with stakeholders around CSR, organizations can achieve CSR objectives (Dobele et al, ) and ensure that organizational decisions and activities are socially acceptable (Green & Hunton‐Clarke, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation